Isolation and identification of Bacillus strains with antimycobacterial activity - El Guendouzi, Souraya (2012)
Tuberculosis is the principal cause of death worldwide due to an infectious disease. The resurgence of tuberculosis, followed by the increase in prevalence of infections caused by nontuberculous mycobacteria (NTM), as well as the multi-drug resistance of mycobacteria to the majority of currently available antibiotics, have encouraged research for new antimycobacterial agents. Soil and water samples from different Moroccan biotopes, have led to the isolation of four bacterial strains (M, R, G and S), showing an inhibitory effect on mycobacterial growth. This effect was shown to be due to secreted substances in the growth medium. From subsequent analysis it was concluded that these strains produced different active substances. Sequencing of the 16S rRNA showed that these isolates belong to the genus Bacillus. The active substance from isolate M, showed the more important inhibitory effect on mycobacterial growth. It is precipitated with ammonium sulfate and lost all activity when treated with Proteinase K, revealing its protein nature.